A User-Centered design and usability testing of a web-based medication reconciliation application integrated in an eHealth network. (June 2019) - Marien, Sophie; Legrand, Delphine; Ramdoyal, Ravi; Nsenga, Jimmy; Ospina, Gustavo; Ramon, Valéry; Spinewine, Anne
Abstract: Background: Medication discrepancies, which are a threat to patient safety, can be reduced by medication reconciliation (MedRec). MedRec is a complex process that can be supported by the use of information technology and patient engagement. Therefore, the SEAMPAT project aims to develop a MedRec IT platform based on two applications. The application for the professionals is called: the "MedRec app". Objective: In the present study, we aimed to describe the development and usability testing of the MedRec app, reporting results of a three iterations user-centered usability evaluation. Methods: We used a three phase iterative user-centered study spread over 16 months. At each phase, the usability evaluation included several methods (observations, questionnaires, and follow-up discussions with participants) to collect quantitative and qualitative data in order to improve the current prototype and evolve to the next prototype. Results: In total, 48 healthcare professionals (25 general practitioners and 23 hospital clinicians) participated to the MedRec app evaluation. There were 14, 32 and 5 participants for phases 1, 2 and 3 respectively. At each phase, many design modifications were done to strengthen usability. Concerning usability, participants considered the prototypes as an acceptable interface with a median System Usability Score of 73 at phase 2 and 75 at phase 3. Participants emphasized the need for improvements concerning workflow integration, usefulness and interoperability. Conclusion: The MedRec app was perceived as being useful, usable and satisfying. However, further improvements are required in several usability aspects. Our study demonstrates the importance of conducting usability assessments before investing time and resources in a large study evaluating the effect of an eMedRec approach on clinical outcomes. Our findings may also increase the chances of acceptability and sustained use over time by clinicians.